Potential of rainwater harvesting for utilizing in urban agriculture (Case study: Mashhad City) - Seyyed Mohammad Seyyed Hosseini; Sayed Mahdi Mostafavi; Arash Dourandish (Atlantic Review of Economics (ARoEc), 2022)
Water scarcity and water issues can be identified as an important challenge to food security, ending hunger and reducing poverty in the 21st century. Therefore, new and effective management mechanisms, along with investment in water technologies and infrastructure, will be needed to reduce the impact of growing water scarcity to mitigate the effects of depleting water resources to ensure that water is allocated for efficient use. One of the new water resources are unconventional resources which received much attention in recent years due to emerging of urban agriculture. One of unconventional resources is rainwater harvesting. Cities, as areas with large levels of impenetrable or low-infiltration lands with different uses, have the potential to harvest significant rainfall. With the rise of urban agriculture and its role in food security, rainwater harvesting seems more necessary than ever. In Iran, a large part of rainwater runoff is wasted, which by collecting and using it, while reducing the risk of flooding, a significant part of this water can be used. Using the information of Khorasan Razavi Meteorological Organization data from 1979 to 2019 (rainfall recorded in the past 30 years in Mashhad synoptic station) and Mashhad Municipality (for occupation area of the buildings) and the model of rainwater harvesting provided by FAO, rainwater harvesting for Mashhad has been mesured. According to residential, commercial and organizations building rooftop area, and based on runoff coefficient of 0.8, rainwater harvesting and storage capacity of 13,535,514,981 liters per year for the city of Mashhad is expected. Based on specific proposed agricultur products and their cultivation requirements, the city of Mashhad can annually produce 73,164,946 kg of tomatoes, 63,250,070 kg of peppers or 63,250,070 kg vegetables, 56,397,979 kg of cucumbers or 56,397,979 kg squash or 67677574/91 kg of lettuce or 67677574/91 kale or 47,493,035 kg of broccoli by utilizing rainwater harvesting.
Keywords: 330; Rainwater harvesting; urban agriculture; Runoff; urban agriculture